EFISIENSI PENGEMBANGAN MEDIA PEMBELAJARAN TEMATIK SISWA KELAS II SEKOLAH DASAR DI SAMARINDA - Marhuma; Mohammad Siddik; Budi Rahardjo (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
This study aims to determine the results of the analysis of the needs of teachers and students, the results of field trials, and the effectiveness test so that they produce appropriate learning thematic teaching materials. This type of research is development research that refers to the ADDIE development model. The research data were obtained from the results of interviews, observation sheets, validation sheets of thematic learning teaching materials, teacher responses and test study results. The results of the assessment of the development of thematic teaching materials, validated by experts, obtained 90% of the very valid conversion results, the analysis of student learning outcomes after using the results of developing thematic teaching materials obtained 90.04% very effective categories. Thematic teaching materials developed by researchers use the ADDIE model that is feasible, effective and efficient to use in the learning process in elementary schools.